In-Flight Analysis and Microstructural Evaluation of CoNiCrAlY Coatings Deposited by HVPS - Caliari, F. R.; Miranda, F. S.; Filho, G. P.; Essiptchouk, A. [UNESP]; Reis, D. A. P.; Azarmi, F.; Balani, K.; Eden, T.; Hussain, T.; Lau, Y. C.; Li, H.; Shinoda, K.; et al. (Asm International, 2018)
The plasma torch design affects the particle-plasma interaction, in-flight properties and the coating microstructure. When spraying metallic powders, the in-flight oxidation as well as the particle velocity and temperature determine the mechanical, corrosion and oxidation properties, which have a major impact on the in-service degradation of bond coats. This study aims to determine the microstructural and mechanical properties of as-sprayed CoNiCrAlY coatings deposited on the Inconel 718 alloy. Depositions were made using a High Velocity Plasma Spray Process (HVPS), which is based on a special plasma torch design. In-flight particle characteristics were determined to elucidate the kinetic and thermal regime of HVPS process.